DEFINITION OF FLOOD HAZARD AREAS VACACAÍ RIVER IN THE CITY OF SAN GABRIEL, RS - Salvadé Silveira, Vanessa; de Souza Robaina, Luis Eduardo; Trentin, Romário (GeoTextos, 2014)
The importance of studies related to flooding and mappings can be observed by the significant increase in research in recent decades. The municipality of São Gabriel, Rio Grande do Su State, has more than 80% of its population in urban areas. Part of this population is located in the nearness of Rio Vacacaí and has subsequently been affected by flood events. This study aims to map the areas with susceptibility and hazard of flooding in the urban area of São Gabriel. The methodological procedures involved the inventory of events, collection and processing of satellite images and topographic data. The analysis and synthesis of information derived from maps. From the analysis of the thirty years it was found that in sixteen years have records of flooding. A total of sixteen years of events were recorded thirty-two where the population was affected with floods. The total susceptibility area is 3.57Km², representing 7.75% of the entire urban area. The danger areas are added to 0.62Km², representing 17.36% within the susceptibility and 1.34% compared to the urban area. This mapping is an important tool to help prevent and reduce natural disasters associated with floods in the study area.